Кореляційно-фазовий інтелектуальний аналіз комплексного ступеню когерентності лазерних автофлуоресцентних зображень плазми крові та діагностика онкологічних змін органів людини - Ушенко, Ю. О.; Дуболазов, О. В.; Солтис, І. В.; Ангельский, А.-П. І.; Ушенко, О. Г.; Гордей, І. Ю.; Ілін, В. А.; Аксинті Воронка, А. Ф. Г. (Vinnytsia National Technical University, 2023)
The theoretical foundations of correlation-phase analysis of laser images of human blood plasma are presented. The values and ranges of change of statistical (moments of the 1st - 4th orders), correlation (Gram-Charlier decomposition coefficients of autocorrelation functions) and fractal (slopes and variance of extremes of logarithmic dependences of power spectra) parameters of the coordinate distributions of CSP are investigated. The objective criteria for diagnosing oncological changes in the blood plasma of a cancer patient are determined.